The Politics of Retaliation: the Backlash of Radical Islamists to the Deradicalization Project in Indonesia - Hilmy, Masdar (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2013)
This paper seeks to analyze how the program of deradicalization in Indonesia is approached, understood and treated by radical Islamists. This paper argues that the deradicalization program in this country has invited controversies, criticisms and even backlash from radical Islamists on the grounds that it goes against the principles of human rights because of stateâs intervention into religious life of its citizens. In addition, it is carried out by violent method which mostly ends with killing the accused terrorists along with the arrest and ambush by security officers. In order to analyze the focus of the study, this paper employs socio-political approach. This paper finds that more thorough approach needs to be employed by the state within the framework of human rights. Therefore, the ideology of radical Islamism and terrorism must be dealt with from two sides; at the upstream and the downstream levels. At the upstream level, the program of deradicalization must be carried out within the framework of interdepartmental and ministerial partnership. This program should invite as many institutions as possible to be involved and reach as wide audience as possible. At the downstream level, the program of deradicalization must abide to human rights principles. The security approach taken by the government should not end with killing or dehumanizing terrorists. By doing so, the national program of deradicalization can appeal as wide sympathy possible and will not harvest backlash from the Islamists. [Artikel ini mendiskusikan bagaimana program deradikalisasi di Indonesia dipahami, dimengerti, dan disikapi oleh kalangan Islamis. Tulisan ini berasumsi bahwa program deradikalisasi yang dilakukan memincu kontroversi, kritik, bahkan memicu juga aksi balasan yang dilancarkan kalangan Islamis radikal. Beberapa kalangan menilai program tersebut melanggar prinsip hak asasi manusia karena merepresentasikan bentuk intervensi negara terhadap kehidupan beragama masyarakatnya. Lebih dari itu, beberapa program dilaksanakan dengan melakukan tindak kekerasan dan kerap berakhir dengan penangkapan, penganiayaan, bahkan pembunuhan tersangka teroris. Dalam menganalisis tema tulisan, pendekatan sosialpolitik digunakan. Artikel ini kemudian menemukan bahwa pendekatan yang berangkat dari nilai-nilai hak asasi manusia perlu dipertegas. Karena itu, ideologi islamis-radikal and terorisme harus dilihat melalui dua sisi secara bersama. Pada level atas, program deradikalisasi dilakukan dengan kerjasama antar lembaga dan kementerian terkait. Dengan begitu, program deradikalisasi diwujudkan dengan mengajak sebanyak-banyaknya lembaga untuk terlibat serta memperluas target audien. Pada level bawah, program deradikalisasi harus mematuhi prinsip hak asasi manusia. Pendekatan keamanan yang dominan dilakukan tidak harus berakhir dengan membunuh atau dengan melanggar hak asasi manusia yang juga melekat pada diri Islamis dan teroris. Dengan model seperti ini, program nasional deradikalisasi mampu memperoleh dukungan dan simpati masyarakat luas dan dapat meredam aksi balasan kalangan Islamis.]